3D Design Modelling of A Quadcopter and The Quadcopter Mechanic using SOLIDWORK and Simulink - Multaza, Mumamad Zulhilmi; Jafferi, Noormaziah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Unmanned aerial vehicle (UAV) which are commonly known as drones is a type of aircraft that doesn’t require a human pilot to maneuver from inside, using a ground-based remote control instead. Classified into few categories, quadcopter is one of many types of UAV that are very well known and has been an increasing interest among generations nowadays. Despite the small in size, this machine has very complex mechanics, which is its movement behavior. The control and stability of a quadcopter is based on not only just the sensors, but also the rotation of each propeller. The step of building a simulation for a quadcopter is to build a 3D model of the quadcopter itself. The design was based on an existing product, E68 drone. This process was done by reverse engineering process. After the 3D model was completed, it was imported into Simulink MATLAB to simulate the quadcopter movement based on the 3 degree of freedom (DOF); roll, pitch and yaw. This quadcopter mechanics were observed via Mechanics Explorer. This simulation can be improved and can be used in wide range of mechanical applications.